BREAKDOWN OF TRUST IN FINANCIAL INSTITUTIONS IN LIGHT OF THE GLOBAL FINANCIAL CRISIS - VAŠKOVÁ, Natália; VAŠKOVÁ, Vanda (Journal of Advanced Studies in Finance, 2010)
Growing interconnectivity of the global economy brings about extensive shocks resulting in increased economic uncertainty. In order for economies to handle these shocks, they need to understand the new normality and design macroprudential policies to increase the stability and resilience of the financial system, necessary for a proper functioning of the world economy. The recent global financial crisis, a turbulence of great magnitude, took the world by surprise and has had an enormous impact on the world economy. One of the negative impacts is a breakdown of trust in financial institutions. Banks are now facing an urgent need to restore public confidence. The objective of this paper is to identify the reasons behind the present global financial crisis and determine actions for banks to take in order to regain the lost trust and build long-term relationships with their clients.